2014
DOI: 10.1186/1471-2407-14-842
|View full text |Cite
|
Sign up to set email alerts
|

Dexrazoxane may prevent doxorubicin-induced DNA damage via depleting both Topoisomerase II isoforms

Abstract: BackgroundThe bisdioxopiperazine dexrazoxane (DRZ) prevents anthracycline-induced heart failure, but its clinical use is limited by uncertain cardioprotective mechanism and by concerns of interference with cancer response to anthracyclines and of long-term safety.MethodsWe investigated the effects of DRZ on the stability of topoisomerases IIα (TOP2A) and IIβ (TOP2B) and on the DNA damage generated by poisoning these enzymes by the anthracycline doxorubicin (DOX).ResultsDRZ given i.p. transiently depleted in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 35 publications
2
90
0
2
Order By: Relevance
“…The works carried out by Lyu et al suggested that proteasomal degradation of TOP2β induced by DXR abolishes DOX-mediated DNA damage in H9c2 cardiomyoblasts [ 66 ]. [ 68 ]. Although DXR mechanisms have not been thoroughly investigated here, our findings support that it is more likely that DXR cardioprotective effect on differentiated H9c2 cells is linked to its interference with DOX on TOP2-mediated DNA cleavage rather than through a metal ion-chelating activity.…”
Section: Figsupporting
confidence: 66%
“…The works carried out by Lyu et al suggested that proteasomal degradation of TOP2β induced by DXR abolishes DOX-mediated DNA damage in H9c2 cardiomyoblasts [ 66 ]. [ 68 ]. Although DXR mechanisms have not been thoroughly investigated here, our findings support that it is more likely that DXR cardioprotective effect on differentiated H9c2 cells is linked to its interference with DOX on TOP2-mediated DNA cleavage rather than through a metal ion-chelating activity.…”
Section: Figsupporting
confidence: 66%
“…Interestingly, cardiomyocytes do not express topoisomerase IIα like tumor cells, but topoisomerase IIβ which can similarly complex with anthracyclines and result in cell death and decreased mitochondrial biogenesis [10, 11]. This is important because dexrozaxane is a cardioprotectant that has been shown to decrease incidence and severity of cardiotoxicity from anthracycline exposure [1214] and acts through inhibition of both isomers of topoisomerase II as well as by chelating free iron and decreasing free radical generation [1517]. …”
Section: Chemotherapeutic Agents That Cause Cardiotoxicitymentioning
confidence: 99%
“…Dexrazoxane reduces the incidence of anthracyclineinduced HF by 80 % and is the only drug approved for its prevention [94]. A recent study demonstrates that dexrazoxane may prevent doxorubicin-induced DNA damage through depleting both topoisomerase II isoforms (Top IIa and b) [95]. Very recently, some investigators provided interesting experimental hints on the use of beta-blockers in the setting of anthracyclines and anti-HER2 treatments [96].…”
Section: The Issue Of Genetic Predispositionmentioning
confidence: 98%